Hexose Kinases and Their Role in Sugar-Sensing and Plant Development - Granot, David; David-Schwartz, Rakefet; Kelly, Gilor (Frontiers in Plant Science, 2013)
Hexose sugars, such as glucose and fructose produced in plants, are ubiquitous in most organisms and are the origin of most of the organic matter found in nature. To be utilized, hexose sugars must first be phosphorylated. The central role of hexose-phosphorylating enzymes has attracted the attention of many researchers, leading to novel discoveries. Only two families of enzymes capable of phosphorylating glucose and fructose have been identified in plants; hexokinases (HXKs) and fructokinases (FRKs). Intensive investigations of these two families in numerous plant species have yielded a wealth of knowledge regarding the genes number, enzymatic characterization, intracellular localization and developmental and physiological roles of several HXKs and FRKs. The emerging picture indicates that HXK and FRK enzymes found at specific intracellular locations play distinct roles in plant metabolism and development. Individual HXKs were shown for the first time to be dual-function enzymes - sensing sugar levels independent of their catalytic activity and also controlling gene expression and major developmental pathways, as well as hormonal interactions. FRK, on the other hand, seems to play a central metabolic role in vascular tissues, controlling the amounts of sugars allocated for vascular development. While a clearer picture of the roles of these two types of enzymes is emerging, many questions remain unsolved, such as the specific tissues and types of cells in which these enzymes function, the roles of individual HXK and FRK genes, and how these enzymes interact with hormones in the regulation of developmental processes. It is anticipated that ongoing efforts will broaden our knowledge of these important plant enzymes and their potential uses in the modification of plant traits.